Evolution of anisotropy in hierarchical porous ceramics during sinter-forging. Issue 12 (September 2016) - Shang, Haixia; Mohanram, Aravind; Olevsky, Eugene; Bordia, Rajendra K.
Abstract: When a body is sintered under non-hydrostatic stress (or strain) fields, anisotropic microstructures may develop which would have an impact on the performance of sintered products. In this study, we focus on the development of pore shape anisotropy during sintering forging. Several parameters were used to characterize the anisotropy of both intrinsic (small inter-particle pores) and extrinsic (large pores from the burnout of pore-formers). The effect of applied stress on grain growth was also investigated. As expected during sinter forging, the pore shape becomes anisotropic and the pores orient preferentially. The intrinsic pores preferentially align parallel while the extrinsic pores align perpendicular to the applied stress. For both intrinsic and extrinsic pores, the degree of anisotropy increases with applied stress, reaches a maximum and then decreases with further increase in stress. Applied stress leads to finer grain microstructures at a particular density. Possible explanations are proposed to explain these observations.